An inadvertently created arteriovenous fistula in the radial artery benefitting the patient for future haemodialysis - Huang, Fangzhong; Zhang, Xingzhen; Lan, Xiaolei; Li, Shuangqing; Huang, Jian (Journal of the Pakistan Medical Association, 2025)
Radial artery puncture is a routine procedure in clinical practice for both diagnostic and therapeutic purposes. Although generally considered safe, rare complications, such as the development of arteriovenous fistula (AVF), can occur. This case report describes the case of a 57-year-old male with stage 5 chronic kidney disease (CKD) who developed an AVF following percutaneous coronary intervention (PCI). Ultrasound evaluation revealed that the AVF had matured sufficiently and was likely to provide adequate blood flow for future haemodialysis. Notably, this inadvertent AVF obviated the need for additional surgical intervention to establish dialysis access. This case highlights the rare but beneficial outcome of AVF formation following radial artery puncture, emphasising the importance of considering anatomical variations and procedural factors during the radial artery puncture. Keywords: Arteriovenous fistula, Radial artery puncture, Haemodialysis, Chronic kidney disease, Percutaneous coronary intervention.